Política e financiamento das universidades estaduais cearenses (2003–2018) no contexto do ajuste fiscal e da desresponsabilização do estado - Bezerra, Jonas Menezes (2022)
This research aims to discuss the financing of state public universities in Ceará (UECE, URCA and UVA) in the period between 2003–2018, corresponding to the administrations of Lúcio Alcântara (2003–2006), Cid Gomes (2007–2014) and Camilo Santana (2015–2018). The three universities, throughout their trajectories, have survived in precarious conditions resulting from the lack of adequate funding. In the period highlighted in this work, despite the particularities of each government, there is a common political project that perpetuates, to a large extent, the political guidelines of the Government of Changes, which we will call “Mudancismo”. Despite the discourse of political modernization and economic development, state universities are not a relevant part of the project of these governments, which has direct repercussions on the continuity of historical underfunding and, consequently, on the precariousness and obstruction of quantitative and qualitative growth of institutions. The argument presented of insufficient resources is questionable in view of the priority established in the state budget for the payment of interest and amortization of the public debt, as well as in the practice of tax exemptions and construction of large works, for example. In the methodological course developed to carry out this investigation, the historicaldialectical materialism is taken as a theoretical-methodological foundation, as it allows the investigation of the object in its totality and concrete existence. As technical procedures, the following were carried out: a survey and bibliographic analysis on the subject; document analysis of the aforementioned government plans and semistructured interviews with relevant political actors from universities and state public higher education. We intend to demonstrate in this work that universities are dispensable in the political project of changing governments, being treated as a political and economic burden for the State. In this way, the precariousness and contention of state institutions is deliberate political option that directly favors the expansion of the private sector, enabling it to respond to the vast demand for access to higher education.